KETERKAITAN FAKTOR DEMOGRAFI DENGAN MOTIF BERPINDAH PILIHAN LAYANAN HOTEL BERBINTANG DI KOTA BENGKULU - Sri Wahyu Putri; Muhartini Salim (Unib Press Universitas Bengkulu, 2017)
The purpose of this research is to examine the relationship between demographic factors and switch motive based on variabels pricing, inconvenience, core service failure, service encounter failure, response to service failure, attraction by the competitor, ethical problems, and involuntary switching. A questionnaire was utilized on 93 respondents of one-star hotels, 61 respondents of two-stars hotels, and 59 respondents of three-stars hotels in Bengkulu City. Analysis technique used is a test cross tabulation. According to the results of this research, the average responses of respondents to switch motive based on variabels pricing, inconvenience, core service failure, service encounter failure, response to service failure, attraction by competitor, ethical problems, and involuntary switching is in high category. The results of this analysis indicate that the overall demographic factors have a significant relationship with the switch motive based on variabels pricing, the core service failure, response to service failure, and ethical problems. However, overall demographic factors exist which hasn't relationship with the switch motive based on variabels inconvenience, service encounter failure, attraction by competitor and involuntary switching.Keywords: Demographic, Pricing, Inconvenience, Core Service Failure, Involuntary Switching.